Information technology project manager's competencies an analysis of performance and personal competencies - Marnewick, Carl (AOSIS, 2016)
The purpose of this book is to shed light on the performance and personal competencies of information technology (IT) project managers in South Africa. Predictive models are built to determine what project managers consider the crucial competencies they should possess to deliver an IT project successfully. This investigation takes place in the context of poor IT project success rates globally and, in particular, in South Africa. This novel research seeks to extend the debate on project success beyond what merely constitutes success or failure, but seeks to find clarity in what IT project managers believe are the essential competencies in practice. This quantitative research gathered data by way of an online survey based on literature regarding the Project Management Competency Development Framework (PMCDF). The population consisted of IT project managers in South Africa. Four hundred and two respondents chose to share their insights. Through the use of descriptive and multivariate statistics, major competency factors were identified. These factors were used in structural equation modelling to build various validated predictive models. This book contributes to the current body of knowledge by uncovering the competencies that IT project managers consider themselves competent in. The structural equation models indicated predictors of perceived competence by IT project managers and where these perceived competencies differ from literature. Twelve managerial implications are highlighted in the final chapter that seek to draw the myriad of threads together into a coherent summary. It is apparent that IT project managers do not consider the PMCDF important in its entirety, but instead choose to focus on certain competencies. This book is intended for reading by fellow researchers as well as project and IT practitioners. These may include IT managers, IT executives, project managers, project team members, the project management office (PMO), general managers and executives that initiate and conduct project-related work. This body of work is original and has not been plagiarised, although certain concepts have been tested in peer reviewed academic work by way of conference proceedings. Instances of this have been referenced and cited. This book is in its first edition and has not been based on thesis work published previously